2021
DOI: 10.1038/s41398-021-01245-6
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of postpartum depression using demographic, clinical, and digital phenotyping

Abstract: Postpartum depression (PPD) and adjustment disorder (AD) affect up to 25% of women after childbirth. However, there are no accurate screening tools for either disorder to identify at-risk mothers and enable them to benefit from early intervention. Combinations of anamnestic, clinical, and remote assessments were evaluated for an early and accurate identification of PPD and AD. Two cohorts of mothers giving birth were included in the study (N = 308 and N = 193). At baseline, participants underwent a detailed so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…It also has the potential to provide precision medicine for the field of psychiatry 22 , better predicting what treatments will work for a particular patient. Although research in digital phenotyping in postpartum women is limited, one study successfully used digitally administered measures to generate three phenotypes of postpartum women, which allowed for early detection of postpartum depression 23 . A review of digital phenotyping for mood disorders in a general population found that digital phenotyping not only has the potential for early detection of mood disorders, but also the capability to capture the nuances of distinct phenotypes of mental illness within a large class.…”
Section: Promisementioning
confidence: 99%
“…It also has the potential to provide precision medicine for the field of psychiatry 22 , better predicting what treatments will work for a particular patient. Although research in digital phenotyping in postpartum women is limited, one study successfully used digitally administered measures to generate three phenotypes of postpartum women, which allowed for early detection of postpartum depression 23 . A review of digital phenotyping for mood disorders in a general population found that digital phenotyping not only has the potential for early detection of mood disorders, but also the capability to capture the nuances of distinct phenotypes of mental illness within a large class.…”
Section: Promisementioning
confidence: 99%
“…However, mental health has been a primary area for the investment and development of this technology. Mental health applications of digital phenotyping include analysis of sleep patterns to predict episodes of relapse in schizophrenia [21], early identification of postpartum depression [22], use of keystroke patterns to predict episodes of mania [23], movement or linguistic analysis to predict episodes of depression [24,25], and social media data used to identify drinking and tobacco abstinence behaviors [26]. Mental health applications have been a primary focus of digital phenotyping projects in part because of the ease with which mobile technology can be used to gather massive amounts of fine-grained behavioral data from the user at any time and in any location [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the early postpartum period is a time known for emotional lability, and depressive and anxious symptoms assessed at this time should be viewed differently than the same symptoms seen prenatally or at later postpartum weeks. Recent research suggests that the EPDS at early postpartum is not reliably able to differentiate between diagnosable postpartum depression and adjustment disorder, but it is a useful tool in differentiating both trajectories from healthy controls [ 35 ]. Importantly, evidence suggests that EPDS scores within the first two days to one week postpartum have a strong predictive power for detecting later postpartum depression [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%